The ontological status of identity: Aristotle adversus Kripke - Martínez Sánchez, Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Saul Kripke has held a notion of essence strongly influenced by identity understood as a necessary property of objects. Asking for essence is to ask for the necessary properties an object must have in order to be that very object. In other words, essence means the necessary conditions of identity. Because of the relation of these questions with the so called contemporary «Aristotelian essentialism», the main subject of this paper consists on a comparison between the Kripkean and the Aristotelian view of identity.